Focus Study on Motivation and Entrepreneur Intention: A Literature Review from Scopus Database - Arika, Deki; Mulyadi, Hari; Nuryanti, B Lena (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This literature review investigates the relationship between motivation and entrepreneurial intention based on data sourced from the Scopus database. Entrepreneurship plays a critical role in economic development and innovation; thus, understanding the motivations behind entrepreneurial intentions is essential. This study systematically reviews 15 relevant documents retrieved using the keywords "Motivation AND Entrepreneur Intention," to synthesize findings from various research perspectives. The review highlights significant fluctuations in research trends over the years, indicating periods of increased interest aligned with economic and social developments, such as the post-COVID-19 era. The analysis reveals that most research is concentrated in Business, Management, and Accounting, with notable contributions from Social Sciences and other multidisciplinary areas. Key themes identified include the impact of social and technological factors on entrepreneurial intentions, variations in motivational factors across different contexts, and the role of entrepreneurship education. The findings suggest that while the research landscape is diverse, there is a need for further exploration into the nuanced and context-specific factors influencing entrepreneurial motivation and intention. This review provides a comprehensive overview of current trends and gaps in the literature, offering valuable insights for policymakers, educators, and future researchers.